Mengintegrasikan Kearifan Lokal ke dalam Pembentukan Karakter Akademik Siswa melalui Pembelajaran Ilmu Sosial - R. Aj. Sofiyah; Siti Faizah; Riska Pristiani (Jurnal Penelitian dan Pendidikan IPS, 2026)
This study aims to analyze and synthesize the integration of local wisdom into Social Studies (IPS) teaching and its implications for the development of academic character in primary school pupils. The scope of the study focuses on a literature review concerning the utilization of local wisdom in Social Studies teaching. The method used is a Systematic Literature Review (SLR) employing the PRISMA approach through the stages of identification, screening, eligibility, and inclusion. A total of 152 articles were retrieved from scientific databases, subsequently screened to yield 6 articles meeting the inclusion criteria. The analysis results indicate that local wisdom is widely utilized as a source of values and a learning context to shape students’ social, moral, and cultural character. However, no studies were found that explicitly examined academic character traits such as study discipline, academic integrity, responsibility towards tasks, and perseverance as a primary focus. Analysis of research trends also indicates that studies remain dominated by developmental and qualitative approaches, with limited use of synthesis-based approaches. Based on these findings, this study proposes a conceptual model that positions local wisdom as a pedagogical foundation in social studies learning to shape academic character through a process of value integration, internalization, and transformation into learning behavior. The study’s conclusions indicate a conceptual gap between the potential of local wisdom and its implementation in the formation of academic character, thus necessitating the development of more targeted learning and assessment models.